MONUMEN MEGALITIK DAN TRANSPORTASI BAHANNYA: Analisis Terhadap Beberapa Faktor Yang Berpengaruh - Lutfi Yondri (Balai Arkeologi Yogyakarta, 2009)
Megalithic monuments in Nusantara are generally found on plateaus, for example on hill tops, mountain slopes, and other remote locations. A big question often raised on how the prehistoric people could move such huge and heavy boulders to build their monuments. It is assumed that to build those megalithic monuments, various factors were involved, i.e. the landscape, technology, and leaderships as well.